2021
DOI: 10.3390/cells10113226
|View full text |Cite
|
Sign up to set email alerts
|

Next- and Third-Generation Sequencing Outperforms Culture-Based Methods in the Diagnosis of Ascitic Fluid Bacterial Infections of ICU Patients

Abstract: Objectives: Infections of the ascitic fluid are serious conditions that require rapid diagnosis and treatment. Ascites is often accompanied by other critical pathologies such as gastrointestinal bleeding and bowel perforation, and infection increases the risk of mortality in intensive care patients. Owing to a relatively low success rate of conventional culture methods in identifying the responsible pathogens, new methods may be helpful to guide antimicrobial therapy and to refine empirical regimens. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The Clostridioides difficile infection is a nosocomial infection due to prolonged exposure to antibiotics [ 25 , 26 ]. In the last decade, the CDI is involving also younger people not undergoing antibiotic therapies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Clostridioides difficile infection is a nosocomial infection due to prolonged exposure to antibiotics [ 25 , 26 ]. In the last decade, the CDI is involving also younger people not undergoing antibiotic therapies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goelz H et al. used the second-generation and third-generation sequencing methods and found that 33 (66%) ascites samples contained Enterobacter faecalis and Klebsiella, and 28 (56%) ascites samples contained anaerobic bacteria ( 165 ). Tuomisto et al.…”
Section: Gut Microbiota and Some Liver Diseasesmentioning
confidence: 99%
“…The case fatality rate of 1 year after the occurrence of ascites is about 15%, and that of 5 years is up to 44%-85% (163,164). Goelz H et al used the second-generation and third-generation sequencing methods and found that 33 (66%) ascites samples contained Enterobacter faecalis and Klebsiella, and 28 (56%) ascites samples contained anaerobic bacteria (165). Tuomisto et al have shown that the number of Gram-negative enterobacter in faeces of patients with alcoholic cirrhosis increases, and enterobacter DNA was detected in ascites up to 50% of patients without spontaneous bacterial peritonitis (166).…”
Section: Cirrhosis and Its Complicationsmentioning
confidence: 99%
“…Recent studies utilizing gene sequencing to identify bacterial pathogens confirmed the latter hypothesis. 7) Finally, other factors should be considered. Etiologies that are currently epidemics are particularly important.…”
mentioning
confidence: 99%